Gestión administrativa de la Dirección Contra el Terrorismo del Perú e influencia en sus operaciones policiales - Tacuna Rubio, José Raúl (2023)
Considering that there are still so-called terrorist remnants affecting the country's internal order, this research aimed to assess the administrative management of the Dirección Contra el Terrorismo de la Policía Nacional del Perú (DIRCOTE PNP) and its influence on police counter-terrorism operations in Peru, 2019. Decreto Supremo N°026-2017-IN dated October 13, 2017, which approves the regulations of Decreto Legislativo N°1267, Ley de la Policía Nacional del Perú (2017), establishes that DIRCOTE PNP "... is responsible for preventing, investigating, fighting and reporting the crime of terrorism" (art. 115); therefore, DIRCOTE PNP must be effectively managed administratively, so as to enable it to efficiently execute its police operations, founding its management on three important indicators: human resources, technological resources, and logistical resources; thus, an applied investigation was conducted, based on a non-experimental design, with DIRCOTE PNP as the unit of analysis, with a sample of 60 members of the police force (officers and non-commissioned officers), collecting data through surveys and using a questionnaire as tool, which enabled the established indicators. Finally, Spearman's Rho was applied, resulting in a value of 0.780, which represents a high degree of positive correlation between the two study variables, hence leading to the conclusion that DIRCOTE PNP's administrative management had a significant influence on police operations against terrorism in Peru, 2019.